Structure-activity relationship studies for the development of inhibitors of murine adipose triglyceride lipase (ATGL). Issue 16 (15th August 2020) - Mayer, Nicole; Schweiger, Martina; Fuchs, Elisabeth; Migglautsch, Anna K.; Doler, Carina; Grabner, Gernot F.; Romauch, Matthias; Melcher, Michaela-Christina; Zechner, Rudolf; Zimmermann, Robert; Breinbauer, Rolf
Graphical abstract: Abstract: High serum fatty acid (FA) levels are causally linked to the development of insulin resistance, which eventually progresses to type 2 diabetes and non-alcoholic fatty liver disease (NAFLD) generalized in the term metabolic syndrome. Adipose triglyceride lipase (ATGL) is the initial enzyme in the hydrolysis of intracellular triacylglycerol (TG) stores, liberating fatty acids that are released from adipocytes into the circulation. Hence, ATGL-specific inhibitors have the potential to lower circulating FA concentrations, and counteract the development of insulin resistance and NAFLD. In this article, we report about structure–activity relationship (SAR) studies of small molecule inhibitors of murine ATGL which led to the development of Atglistatin. Atglistatin is a specific inhibitor of murine ATGL, which has proven useful for the validation of ATGL as a potential drug target.